Smart mirror technology: Influence on luxury fashion retail consumers - Meireles, P.; Dias, Á. L.; Lisboa, A. C. C.; Pereira, L. F. (Asia Pacific Journal of Marketing and Logistics)
Purpose This study investigates smart mirror technology’s impact on luxury fashion retail consumers, namely its influence on consumer satisfaction and purchase intentions. By extending the Technology Acceptance Model (TAM) to include aesthetic appeal and navigation, the research addresses gaps in understanding the adoption of in-store technologies in high-end retail environments. Design/methodology/approach The research uses a quantitative approach, via a survey conducted among luxury fashion consumers. Partial least squares structural equation modeling and combined importance-performance map were employed to test the proposed relationships. Findings Results reveal that perceived usefulness and navigation influence consumer satisfaction with smart mirror experiences, which, in turn, drive purchase intention. Conversely, perceived ease of use and aesthetic appeal did not significantly affect satisfaction. Navigation emerged as the most critical experiential factor, underscoring the importance of seamless and intuitive interactions for luxury consumers. Research limitations/implications The reliance on video-based simulations instead of real-world interactions may limit the validity of the findings. The focus on luxury fashion restricts generalizability to other retail segments. Future research should involve in-store experiments and consider other technologies or consumer segments. Practical implications Luxury retailers should prioritize the design of intuitive navigation and functional features in smart mirrors to enhance consumer satisfaction and encourage purchase behavior. Integrating digital elements should complement, rather than replace, personalized human service to maintain the high-touch experience expected in luxury contexts. Originality/value This research contributes to the literature by extending TAM in a luxury retail context, namely navigation and aesthetic appeal. The study contextualizes technology adoption within high-touch, hedonic retail environments.